Estimation of the undrained shear strength of Adapazari fine grained soils by cone penetration test - Bol, Ertan; Özocak, Aşkın; Sert, Sedat; ÖNALP, AKIN (ELSEVIER, RADARWEG 29, 1043 NX AMSTERDAM, NETHERLANDS, 2019)
A comprehensive study to determine the undrained shearing resistance of fine grained soils by the use of cone penetration test (CPTu) was carried out on the thick fluvial sediments of the plain of Adapazari, Turkey. The soundings were performed adjacent to geotechnical boreholes for comparison. Eighty-three undisturbed samples of low, intermediate and high plasticity were procured in the process, which were classified and tested in unconsolidated undrained triaxial (UU) conditions in the laboratory. The cone resistance, sleeve friction and pore water pressure values recorded along the length of undisturbed sampling were averaged to obtain characteristic values. It is known that the empirical formulae to interpret CPT readings use cone factors N-k, N-kt and N-ke which can be highly variable. This can lead to unacceptable error levels in the assessment of undrained shear strength (s(u)). Nevertheless, it was noticed in this study that the undrained strengths estimated by employing the traditional relationships for CPT came out quite close to the values measured in the laboratory if soil classes are taken into account. Since soil sampling is not done in the cone penetration test by default, classification of the soil is attempted by the use of the soil type behavior index (I-c) This study showed that the error margins for s(u) values measured in the laboratory and inferred from CPT are considerably reduced by using the soil type behavior index (I-c) to determine soil behavior type specific cone factors.
Keywords: Cone Penetration Test; Tip Resistance; Sleeve Friction; Undrained Shear Strength; Triaxial Test; Soil Behavior Type Index